Applications of nanotechnology in concrete design proceedings of the international conference held at the University of Dundee, Scotland UK on 7 July 2005 - Dhir, Ravindra K.; Newlands, Moray D.; Csetenyi, Laszlo J. (Thomas Telford, 2005)
For opportunities to change into beneficial practice, engineers, material scientists, architects, manufacturers and suppliers must focus on the changes that are required to champion concrete and maintain its dominance within the global construction industry. This conference was organised to address these changes.